The Mitochondrial Fission Receptor MiD51 Requires ADP as a Cofactor - Losón, Oliver C. (2014)
Mitochondrial fission requires recruitment of dynamin-related protein 1 (Drp1) to the mitochondrial surface and activation of its GTP-dependent scission function. The Drp1 receptors MiD49 and MiD51 recruit Drp1 to facilitate mitochondrial fission, but their mechanism of action is poorly understood. Using X-ray crystallography, we demonstrate that MiD51 contains a nucleotidyl transferase domain that binds ADP with high affinity. MiD51 recruits Drp1 via a surface loop that functions independently of ADP binding. However, in the absence of nucleotide binding, the recruited Drp1 cannot be activated for fission. Purified MiD51 strongly inhibits Drp1 assembly and GTP hydrolysis in the absence of ADP. Addition of ADP relieves this inhibition and promotes Drp1 assembly into spirals with enhanced GTP hydrolysis. Our results reveal ADP as an essential cofactor for MiD51 during mitochondrial fission.